Accelerating computational analyses of low velocity impact and compression after impact of laminated composite materials. (15th March 2021) - Lin, Shiyao; Waas, Anthony M.
Abstract: Computational time can be significantly reduced in the analysis of low velocity impact (LVI) and compression after impact (CAI) response of composite materials with the method proposed in this paper. Because of the complexity of the problem and the necessity to capture the damage details with sufficient fidelity, existing computational models usually take days to run even on high performance computing (HPC) clusters. A framework to reduce computational time by adopting a smart mesh paradigm, an efficient modeling strategy, and a damage state transferring algorithm between the LVI and CAI meshes is proposed. The model is validated against the LVI and CAI experimental results of a [45/−45/0/45/−45/90/45/−45/45/−45]s T800s/3900-2B laminate with impact energy below the barely visible impact damage (BVID) limit. Compared to prior computational models, the computational time of the new approach leads to a 67% reduction, while correctly capturing damage patterns and accurately predicting compressive strength after impact.